The Effect of Educational Video Media Use on Knowledge of Balanced Eating Patterns in School-Age Children at SDN Serua 3 Depok - Muhammad Abhista Hakim; Avliya Quratul Marjan (Abdimas Indonesian Journal, 2026)
Nutritional issues among school-aged children remain a challenge in Indonesia, including in the Bojongsari Community Health Center work area. Children are at risk of malnutrition or overnutrition due to diets that do not follow balanced nutrition guidelines, such as consuming fast food high in sugar, salt, and fat. This condition can affect children's health, growth, and academic performance. Therefore, effective educational interventions are needed to improve children's understanding of healthy eating habits. This activity aimed to determine the effect of animated educational video media on balanced nutrition knowledge in school-aged children. The intervention was conducted offline at SDN Serua 3, Depok City, involving 30 fifth-grade students. The animated video "Super Gizi Squad" was combined with interactive activities such as recall games, guessing the picture, and pre- and post-tests. The results showed improved knowledge. Before the intervention, 66.7% of students had poor knowledge, 30% sufficient, and 3.3% good. After the intervention, 76.7% had sufficient knowledge and 23.3% good, with no poor category. The average score increased from 60.07 to 80.17, indicating significant improvement. In conclusion, animated educational videos effectively improve children's knowledge of balanced nutrition..